Assessment of left ventricular diastolic dysfunction following anthracyclinebased chemotherapy in breast cancer patients - A. N. Sumin; A. V. Shcheglova; Yu. S. Slepynina; A. V. Ivanova; O. M. Polikutina (Acta Biomedica Scientifica, 2022)
Cardiotoxicity is a side effect of anthracycline-based chemotherapy. Clinical and prognostic significance of left ventricular diastolic dysfunction in heart failure patients is undeniable.The aim. To assess dynamic changes in the left ventricular diastolic function after anthracycline-based chemotherapy (ANT) in breast cancer patients.Material and methods. The study included 40 women aged 35 to 72 years with breast cancer (BC) undergoing ANT chemotherapy. The main group (n = 40) consisted of women with breast cancer examined at admission, after 6 months the same women (n = 37) were examined again. Women without breast cancer (n = 25) were used as the control group.Results. Dynamic changes in mitral annular velocities were revealed by Doppler tissue imaging. Lateral early diastolic mitral annular velocity (e’ lateral) was significantly lower in breast cancer patients as compared to the control group (p = 0.031). Six months after ANT chemotherapy, there was a definite increase in the lateral late diastolic mitral annular velocity (a’ lateral) (p = 0.033). Average early diastolic transmitral flow velocity to early diastolic velocity (E/e’ lateral) ratio was within the normative values in all groups, but E/e’ lateral in the main group was higher compared to the control group (p = 0.003). In the main group, septal early diastolic mitral annular velocity (e’ septal) was lower compared to the control group (p = 0.0005). Moreover, an increase in the septal mitral annular velocity (a’ septal) (p = 0.01) and higher E/e’ septal ratio (p = 0.011) were revealed during dynamic observation. Multiple logistic regression disclosed that E/A, e’ lateral, e’/a’ lateral, and E/e’ lateral were affected by heart rate, psychological status, age, hypertension, and body mass index, but not anthracycline chemotherapy. The total dose of anthracycline was independently associated with e’ septal and E/e’ septal: F(4.18) = 16.466 (p < 0.001; R2 = 0.775) and F(3.16) = 7.271 (p = 0.004; R2 = 0.627).Conclusion. Left ventricular diastolic function worsens in women undergoing anthracycline-based chemotherapy for breast cancer (lower e’, e’/a’ lateral, and e’ septal, higher E/e’ septal ratio). However, anthracycline does not significantly affect LVEF and LV deformation indicators. E/e’ septalande’ septal are independently associated with the total dose of anthracycline.